Formation of the theory and practice of physical education in the Soviet Ukraine through the prism of reforming pedagogy (1920 - 1930). - Lukjanchenko M.I (Kharkov National Pedagogical University, 2010)
In the article has been analysed the development of physical education in the 20th of XX century in Ukraine. It is set that physical education in the period named above is selected as a general pedagogical problem; the main trends in theory and practice of physical education have been revealed. Basic progress of theory and practice of physical education trends are considered. It is certain that sports and mass work with young people and physical education had military direction, the purpose of which was education of man-patriot, able to protect Fatherland. Maintenance of science is exposed «pedology».